The interplay between gender-based workplace prejudice and girls’ occupational choice at Bahir Dar polytechnic college - Melaku Mengistu Gebremeskel (Bahir Dar Journal of Education)
This study aims to pin down whether there is linearity between genderbased occupational stereotyping and the professional choice of girls at Bahir Dar Polytechnic College. Four interrelated basic questions treated through qualitative design were emphasized to spearhead the study. Thirteen female students and one key informant took part in the study. The analysis and interpretation of data demonstrated that the gender-based workplace labeling has put over its own impact on the professional choice of girls in the college. That is, the professional gender context in the college is the reflection of the gender stratification that exists in the wider society in general and in the work place practices in particular. It also revealed that efforts made so far by the college to minimize the genderbased occupational labeling have been more of futile exercises. The problem of gender stereotyping in the college is, therefore, not that much pushed over except the placement of as many girls as possible in traditionally male-dominated occupations through a quota system.